Application of Acrylic‐Rubber‐Based Latex Binder to High‐Voltage Spinel Electrodes of Lithium‐Ion Batteries. Issue 19 (2nd October 2019) - Hitomi, Shoichi; Kubota, Kei; Horiba, Tatsuo; Hida, Kazuo; Matsuyama, Takashi; Oji, Hiroshi; Yasuno, Satoshi; Komaba, Shinichi
Abstract: Acrylic rubber (AR) is studied as a new aqueous latex binder for a high‐voltage positive electrode material, spinel‐type LiNi0.5 Mn1.5 O4, for lithium‐ion batteries (LIBs). The electrode with AR and sodium carboxymethyl cellulose (CMC) as a composite binder delivers a reversible capacity of 138 mAh g −1 at the first cycle and 128 mAh g −1 at 50th cycle in non‐aqueous Li cells within a voltage range of 3.0 to 5.0 V. As well as capacities higher than 120 mAh g −1, in the case of conventional poly(vinylidene fluoride) (PVdF) binder, the AR/CMC electrode exhibits better cycle stability than that with PVdF. An initial coulombic efficiency of the AR/CMC electrode of 91 % is higher than 78 % for the styrene‐butadiene rubber (SBR)/CMC electrode, because irreversible anodic oxidation of a C=C bond in the SBR molecule is avoided in the AR molecular structure. In addition, comprehensive analyses with AC impedance spectroscopy, cross‐sectional scanning electron microscopy, X‐ray diffraction, time‐of‐flight secondary‐ion mass spectrometry, as well as hard and soft X‐ray photoelectron spectroscopy reveal uniform dispersion of LiNi0.5 Mn1.5 O4 particles and acetylene black in the AR/CMC electrode and sufficient coverage of AR/CMC on LiNi0.5 Mn1.5 O4 particles due to good affinity of aqueous binder to them. Abstract : In a bind : Acrylic rubber (AR) is studied as a new aqueous latex binder for a high‐voltage positive electrode material, spinel‐type LiNi0.5 Mn1.5 O4, (LNMO), in lithium‐ion batteries. LNMO electrodes with AR/sodium carboxymethylcellulose binary binder show better initial coulombic efficiencies and cyclability than those with conventional poly(vinylidene fluoride) binder.